Postbiotic Metabolite Derived from Lactiplantibacillus plantarum PD18 Maintains the Integrity of Cell Barriers and Affects Biomarkers Associated with Periodontal Disease - Widawal Butrungrod; Chaiyavat Chaiyasut; Netnapa Makhamrueang; Sartjin Peerajan; Wantida Chaiyana; Sasithorn Sirilun (MDPI AG, 2024)
Background/Objectives: Periodontal disease is caused by oral infections, biofilms, persistent inflammation, and degeneration of cell barrier integrity, allowing pathogens to invade host cells. Probiotics have been extensively studied for the treatment of periodontal disease. However, research on the involvement of beneficial substances produced by probiotics, called "postbiotics," in periodontal diseases remains in its early stages. The present study aimed to evaluate the effect of a postbiotic metabolite (PM) from Lactiplantibacillus plantarum PD18 on immunomodulation and maintenance of cell barrier integrity related to periodontal disease. Method: The main substance in PM PD18 was analyzed by GC-MS. The cytotoxic effect of PM PD18 was performed using the MTT assay, wound healing through the scratch assay, cell permeability through TEER value, modulation of inflammatory cytokines through ELISA, and gene expression of inflammatory cytokines and tight junction protein was determined using qRT-PCR. Results: The main substance found in PM PD18 is 2,3,5,6-tetramethylpyrazine. PM PD18 did not exhibit cytotoxic effects on RAW 264.7 cells but promoted wound healing and had an antiadhesion effect on Porphyromonas gingivalis concerning SF-TY cells. This postbiotic could maintain cell barrier integrity by balancing transepithelial electrical resistance (TEER) and alkaline phosphatase (ALP) activity. In addition, the gene and protein expression levels of zonula occludens-1 (ZO-1) increased. PM PD18 was found to have immunomodulatory properties, as demonstrated by regulated anti- and pro-inflammatory cytokines. Interleukin-10 (IL-10) increased, while IL-6 and IL-8 were reduced. Conclusions: This study demonstrated that PM PD18 is efficient as a natural treatment for maintaining cell barrier integrity and balancing inflammatory responses associated with periodontal disease.